Silent spread of poliovirus type 2 variant (cVDPV) in Gaza - Mohd Sayeed Shaikh; Md. Faiyazuddin; Syed Sarfaraz Ali; Israrul H Ansari; Sanjit Sah; Rachana Mehta (The Egyptian Journal of Internal Medicine)
Abstract The silent spread of circulating vaccine-derived poliovirus type 2 (cVDPV2) in Gaza has become a major public health emergency, exacerbated by ongoing conflict, inadequate sanitation, and limited healthcare access. The virus was discovered in sewage samples from Khan Younis and Deir al Balah, and genetic analysis linked it to a strain found in Egypt in late 2023. The first polio case in Gaza in 25 years was confirmed in August 2024 in a 10-month-old child. This review explores the epidemiology of cVDPV2 in Gaza, its relationship to regional strains, and the risk factors that exacerbate transmission. It describes the role of various polio vaccines, including the novel oral polio vaccine type 2 (nOPV2), in emergency campaigns coordinated by WHO, UNICEF, and the Palestinian Ministry of Health. The review further explores into Gaza’s unique “Gaza system” of combined vaccination, the challenges of maintaining cold-chain logistics, and the significance of wastewater surveillance. To contain the outbreak and prevent poliomyelitis from resurging in vulnerable populations, humanitarian access, ceasefire enforcement, and global cooperation are urgently needed.